Liquid exfoliated SnP3 nanosheets for very high areal capacity Lithium-Ion Batteries - Tian, Ruiyuan; Griffin, Aideen; McCrystall, Mark; Breshears, Madeleine; Harvey, Andrew; Gabbett, Cian; Horváth, Dominik V.; Backes, Claudia; Jing, Yu; Heine, Thomas; Park, Sang-Hoon; Coelho, João; et al. (Advanced energy materials, 2021)
Increasing the energy density of lithium-ion batteries requires the discovery of new electrode materials capable of achieving very high areal capacity. Here, liquid phase exfoliation is used to produce nanosheets of SnP3, a 2D material with extremely high theoretical capacity of 1670 mAh g−1. These nanosheets can be fabricated into solution-processed thin films for use as lithium storing anodes. To maximize their performance, carbon nanotubes are incorporated into the electrodes to simultaneously enhance conductivity and toughness. As a result, electrodes of thickness >300 µm can be produced, which display active-mass-normalized capacities (≈1657 mAh g−1Active) very close to the theoretical value. These materials show maximum specific (≈1250 mAh g−1Electrode) and areal (>20 mAh cm−2) capacities, which are at the state-of-the-art for 2D-based electrodes, coupled with good rate performance and stability. In combination with commercial cathode materials, full-cells are fabricated with areal capacities of ≈29 mAh cm−2 and near-record energy densities approaching 1000 Wh L−1.